Clinical and Laboratory Features of Culture-positive Neonatal Sepsis: A 5-year Single-center Experience at Tertiary Neonatal Intensive Care Unit in Turkey - Aydin, Mustafa; Ozeren, Isilay; Orman, Aysen; Benli, Samet; Hakan, Nilay; Tasin, Erdal (Galenos Publ House, 2024)
Objective: Neonatal sepsis is an important cause of neonatal mortality and morbidity, especially in low birthweight premature babies. This study aimed to examine the clinical and laboratory features of cases with culturepositive neonatal sepsis. Method: Medical records of 233 newborn infants with culture -positive sepsis among 4241 hospitalized patients between January 2013 and December 2017 were reviewed. Demographic and clinical data of these patients were retrospectively recorded. Results: The majority of patients was extremely and moderately preterm infants (39.1% vs. 11.6%). These patients had a history of invasive mechanical ventilation (74. 2%) or central catheterization (26.9%). The mostly isolated pathogens (56. 2%) were Gram-negative bacteria, especially Klebsiella pneumoniae in 67 (28. 8%) cases. Post -hoc test showed a statistically significant difference in the incidence rates of leukopenia between patients infected with Gram-positive, Gram-negative bacteria and fungi (12. 3%, 16.8% and 17.2%, respectively) (p=0.021). Patients who developed leukopenia (n=36, 15.5%) had a higher mortality rate compared to those with leukocytosis (n=50, 21.5%) (72.2% vs. 50%, p<0.001). The duration of total parenteral nutrition was found to be a significant risk factor in terms of mortality (p=0.015). Conclusion: Prolonged parenteral nutrition is an important risk factor for mortality in low -birth weight newborns and those with sepsis. It is noteworthy that the mortality rate is higher in newborns with sepsis who developed leukopenia and neutropenia.
Keywords: Newborn; microorganism; risk factors; sepsis; prognosis